Use of recombinant proteins in the diagnosis of sexually transmitted infections: a systematic review and meta-analysis (Research, Society and Development, 2022)
The present systematic review and meta-analysis aimed to investigate the use of recombinant proteins to diagnose STIs and evaluate the performance of the tests identified. The databases, SciELO, PubMed, CAPES Journal Portal, and LILACS, were searched according to the PRISMA protocol. A study was considered eligible if it met previously defined criteria. The risk of study bias was assessed according to the QUADAS-2 protocol. The meta-analysis was performed based on the random-effects model, and heterogeneity was quantified using the I² statistic. A total of 1,355 studies were selected, 30 of which were relevant to the following: human immunodeficiency virus (12/30), Treponema pallidum (10/30), Chlamydia trachomatis (3/30), herpes simplex virus (HSV, 2/30), Trichomonas vaginalis (2/30), and HSV/cytomegalovirus (1/30). The main serological tests were ELISA and immunochromatography. The risk of bias was low for most included studies. According to each microorganism, the meta-analysis revealed satisfactory sensitivity and specificity for the analyzed tests. The findings reinforce the relevance of diagnostic tests based on recombinant proteins as viable alternatives for production and inclusion in clinical practice. PROSPERO registration number: CRD42020206331.